Role of autophagy and mTOR signaling in neural differentiation of bone marrow mesenchymal stem cells. (18th August 2014) - Li, Yanfei; Wang, Cuiqin; Zhang, Guangyu; Wang, Xiaohan; Duan, Ranran; Gao, Huili; Peng, Tao; Teng, Junfang; Jia, Yanjie
Abstract Autophagy is involved in cell differentiation. We present evidence that autophagy is activated during β‐mercaptoethanol (β‐ME)‐induced neuronal differentiation of bone marrow mesenchymal stem cells (MSCs), in which mammalian target of rapamycin (mTOR) signaling is important. mTOR activity declined after being transported from the nucleus to the cytoplasm. Using 3‐methyladenine (3‐MA) and rapamycin to regulate the activity of mTOR, it was found that the efficiency of neuronal differentiation was affected.